The Effects of Store Atmospher Cafe Interior to Purchase Intention on Cafe My Kopi O! Malang - Nenchi Rana Mustika; Herry Santosa (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Malang City has a culinary cafe business level that increased from year to year. Culinary is not only a fulfillment of primary but has become part of the lifestyle of the community. Eating or drinking activities in a cafe has shifted into activities for meetings or gatherings and enjoy the atmosphere and can capture the moment at the cafe. This can provide opportunities for entrepreneurs in the culinary business to be able to provide facilities and createagoodcafeatmosphereatthecafe.Thepurposeofthisstudywastofindouthowthe influenceofthegeneralinterioronpurchaseintentioninMyKopiO!Malangusingmultiple linear regression analysis. This study used descriptive-quantitative method. Respondent sample in this study taken from 105 Cafe visitors My Kopi O! by using a non-probability sampling method with a purposive sampling technique. The results of this study indicate that the general interior is the most influential especially in the aspect of wall texture. General interior has an influenceon purchase intentionof 57.5%and the remaining 42.5% isinfluencedbyotherfactors.Keywords:StoreAtmosphere,GeneralInterior,PurchaseIntention,Café,Descriptivequantitative